Mapping Climate Change Research Collaboration in Tanzania from 1964 to 2021: A Bibliometric Analysis - Muneja, Paul Samwel (University of Dar es Salaam Library Journal, 2024)
This study explored research collaboration in climate change initiatives in Tanzania. Specifically, it sought to uncover the collaborative networks of researchers based on Tanzania’s climate change research outputs from 1964 to 2021. A bibliometric approach was used to analyse co-authorship as an indicator of research collaboration during the investigated period. Data were researched and retrieved from the Dimensions.ai database based on specified keywords. VOSviewer software was employed to analyse the data and obtain co-authorship networks, while MS Excel was used to organise and analyse the frequency data percentages. The results have revealed that researchers from Tanzania have a strong collaborative network with other countries in climate change research. Additionally, researchers from the University of Dar es Salaam seem to have stronger collaborative ties with those from the Sokoine University of Agriculture and the Nelson Mandela African Institute of Science and Technology. International researchers with significant co-authorship alongside Tanzanian researchers come from the United States, the United Kingdom, Germany, Kenya, and South Africa respectively. Furthermore, the results indicate that developed countries such as the US, UK, Germany, and South Africa, despite co-authoring only a few publications, seem to exhibit a high total link strength. Therefore, research collaboration in its various manifestations and levels needs encouragement, as it enhances both the quality and quantity of research output productivity. There is a need to strengthen research collaboration on climate change between researchers from Tanzania and those from African nations to establish local climate change mitigation measures that suit the African environment. Further studies should focus on the motivations for research collaboration and the funding patterns of collaborations within the country. Keywords: Bibliometrics, climate change, research collaboration, research productivity, Tanzania https://dx.doi.org/10.4314/udslj.v19i2.4